Histological classification of 1,025 cases of Hodgkin’s lymphoma from the State of São Paulo, Brazil - Vassallo, José; Paes, Roberto Pinto; Soares, Fernando Augusto; Menezes, Yara; Aldred, Vera; Ribeiro, Karina de Cássia Braga; Alves, Antonio Correa (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: It is currently asserted that, in industrialized countries, nodular sclerosis is the most frequent type of Hodgkin’s lymphoma, in contrast to developing countries, where mixed cellularity and lymphocyte depletion are more frequently seen. The objective was to review histological data from cases of Hodgkin’s lymphoma from São Paulo and Campinas cities. DESIGN AND SETTING: Cross-sectional histo- pathological analysis, in four university hospitals and one cancer care center. METHODS: 1,025 cases diagnosed as Hodgkin’s lymphoma between 1990 and 2000 were col- lected from ﬁve institutions; 631 of them (61.5%) had been immunophenotyped using antibodies to CD20, CD3, CD15 and CD30. The relative frequencies of histological types (as informed by the contributing authors, who are hematopathologists in their institutions) were determined according to age and gender. RESULTS: The Hodgkin’s lymphoma types were distributed as follows: lymphocyte predominance 4.8%, nodular sclerosis 69.2%, mixed cellularity 21.1% and lymphocyte depletion 4.6%. CONCLUSIONS: The controversy regarding the frequencies of Hodgkin’s lymphoma types within the Brazilian setting seems to be due to the small number of cases in previous studies. The present data show a picture close to the situation in the industrialized countries.